Impact of human adipose tissue-derived stem cells on malignant melanoma cells in an in vitro co-culture model - Preisner, Fabian; Zörnig, Inka; Germann, Günter (Stem cell reviews and reports, 2018)
This study focuses on the interactions of human adipose tissue-derived stem cells (ADSCs) and malignant melanoma cells (MMCs) with regard to future cell-based skin therapies. The aim was to identify potential oncological risks as ADSCs could unintentionally be sited within the proximity of the tumor microenvironment of MMCs. An indirect co-culture model was used to analyze interactions between ADSCs and four different established melanoma cell lines (G-361, SK-Mel-5, MeWo and A2058) as well as two low-passage primary melanoma cell cultures (M1 and M2). Doubling time, migration and invasion, angiogenesis, quantitative real-time PCR of 229 tumor-associated genes and multiplex protein assays of 20 chemokines and growth factors and eight matrix metalloproteinases (MMPs) were evaluated. Co-culture with ADSCs significantly increased migration capacity of G-361, SK-Mel-5, A2058, MeWo and M1 and invasion capacity of G-361, SK-Mel-5 and A2058 melanoma cells. Furthermore, conditioned media from all ADSC-MMC-co-cultures induced tube formation in an angiogenesis assay in vitro. Gene expression analysis of ADSCs and MMCs, especially of low-passage melanoma cell cultures, revealed an increased expression of various genes with tumor-promoting activities, such as CXCL12, PTGS2, IL-6, and HGF upon ADSC-MMC-co-culture. In this context, a significant increase (up to 5,145-fold) in the expression of numerous tumor-associated proteins could be observed, e.g. several pro-angiogenic factors, such as VEGF, IL-8, and CCL2, as well as different matrix metalloproteinases, especially MMP-2. In conclusion, the current report clearly demonstrates that a bi-directional crosstalk between ADSCs and melanoma cells can enhance different malignant properties of melanoma cells in vitro.
Published online: 24 October 2017
Gesehen am 11.05.2020